Antiulcerogenic activity of the aqueous fraction of Anacardium humile St. Hil (Anacardiaceae) - Ferreira, Anderson Luiz; Cola, Maíra; Barbastefano, Vitor; Hiruma-Lima, Clélia Akiko [UNESP]; Santos, Lourdes Campaner dos [UNESP]; Vilegas, Wagner [UNESP]; Brito, Alba Regina Monteiro Souza (Academic Journals, 2012)
Anacardium humile St. Hil. is being used in traditional medicine to treat ulcer. The present work evaluated the mechanisms of action involved in the anti-ulcer properties of the aqueous fraction from leaves of A. humile (AHQ). Gastroprotection of A. humile was evaluated in ethanol and piroxicam models. Mechanisms of action such as mucus production, nitric oxide (NO), sulfhydryl compounds (SH) and the anti-secretory action were evaluated. The acetic acid-induced gastric ulcer model was used to evaluate the A. humile healing properties. Results obtained in the ethanol model showed that AHQ provided significant gastroprotection at all the tested doses (50, 100, and 200 mg/kg). Thereby, the following protocols were performed using the dose capable of producing the most effective gastroprotection, which was the AHQ 200 mg/kg (P < 0.001). Moreover, AHQ (200 mg/kg) protected the mucosa from piroxicam-induced damage. Mucus, NO, and SH did not participate on this gastroprotection. AHQ interfere in H+ secretion in gastric mucosa, thus exerting an anti-secretory activity. Our results suggest that the gastroprotection and cicatrisation process executed by AHQ occurred due to its anti-secretory activity. This study reinforces its traditional medicinal use. Considering that the current therapies are based on the use of anti-secretory agents, the A. humile arises as a promising alternative antiulcer therapy.
Keywords: Anacardium humile St. Hil.; Gastric ulcer; Gastroprotection